2018
DOI: 10.21608/ejbo.2018.3423.1166
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seed presoaking with KNO3 on seed germination, proline, protein pattern, ß-Amylase and mineral compositions of two faba bean cultivars treated with NaCl

Abstract: Different salinization levels (0, 40, 80, 120 and 160mM NaCl) were used and both cultivars were presoaked in either water (Reference control) or potassium nitrate (3mM), then left for germination for five days. Plants transported to the field and further growth for 65 days from sowing. The final germination percentage the two broad bean cultivars of Vicia faba c were decreased by increasing salinity in the rooting medium. Seed presoaking in KNO 3 resulted in remarkable increase in final germination percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…However, previous studies showed that nutrient availability significantly enhances seedling growth rate, improving their establishment (Maun, 1994;Del Vecchio et al, 2013) by incrementing seedling biomass (Frosini et al, 2012), and counteracting the effect of sand burial (Gilbert et al, 2008). Similarly to nitrogen alone, the interaction of nitrogen and salinity also seems to be particularly important during the post-germination phase: nitrogen supply proved to alleviate the toxic effect of salinity in seedlings, enhancing the activity of antioxidant enzymes in several species (Zheng et al, 2008;Abd El-Baki et al, 2018;Ibrahim et al, 2018). Therefore, we could affirm that nutrients such as nitrogen could limit species survival in adults but seems to have a less important role in the germination of coastal species.…”
Section: Effect Of Nitrogenmentioning
confidence: 97%
See 1 more Smart Citation
“…However, previous studies showed that nutrient availability significantly enhances seedling growth rate, improving their establishment (Maun, 1994;Del Vecchio et al, 2013) by incrementing seedling biomass (Frosini et al, 2012), and counteracting the effect of sand burial (Gilbert et al, 2008). Similarly to nitrogen alone, the interaction of nitrogen and salinity also seems to be particularly important during the post-germination phase: nitrogen supply proved to alleviate the toxic effect of salinity in seedlings, enhancing the activity of antioxidant enzymes in several species (Zheng et al, 2008;Abd El-Baki et al, 2018;Ibrahim et al, 2018). Therefore, we could affirm that nutrients such as nitrogen could limit species survival in adults but seems to have a less important role in the germination of coastal species.…”
Section: Effect Of Nitrogenmentioning
confidence: 97%
“…Specifically, KNO 3 has been proven to alleviate salt-induced stress in several species (Neid & Biesboer, 2005;Atia et al, 2009;Zehra et al, 2013) including Elymus farctus (El-Katony et al, 2015). Conversely, KNO 3 could not alleviate the effect of salinity in Silene mollissima aggregate (Murru et al, 2015) and in Vicia faba (Abd El-Baki et al, 2018). However, unlike salinity and temperature, which in general decrease linearly from the sea DEL VECCHIO Et aL.…”
Section: Introductionmentioning
confidence: 99%